Identity at Work: An Enquiry‐based Approach to Therapeutically Inspired Management. (July 2017) - Beech, Nic
Abstract: Identity studies reveal many issues and problems for individuals and organizations and from these I select three topics which connect to management practice: performance and its barriers; the self and others; and boundaries and transitions. I argue for an enquiry‐based approach to management practice which focuses not on prescriptive answers but on engaging questions which can draw on theory as a resource and promote thought‐infused action. Because much of the identity literature would be sceptical about normative theory 'implications for practice' tend to be somewhat thin. An enquiry‐based approach removes normative expectations along with the hierarchical expectation that theory is first and practice is second. Rather, practice‐relevant questions can be refined and developed through theoretical engagement. An enquiry that has practical relevance is also likely to draw resource from across disciplinary boundaries, and in this case I draw on ideas from therapeutic theory to challenge and support management practice.